FEATURES OF EVOLUTIONARY DEVELOPMENT FOR SMALL AND MID-SCALE BUSINESSES OPERATING ON THE SPHERE OF CONSUMER SERVICE - Elena N. Bogdanova (Вестник Северо-Кавказского федерального университета, 2022)
The paper identifies factors constraining the development of small businesses in the consumer services sector; there is also a view on the tasks faced by the Russian economy where small businesses could have a positive impact, as well as the parallels shown between the standard of living and the development of small and mid-scale businesses